An Exploration of Ethnic Dynamics in Nepal (Journal of Population and Development, 2020)
This article explores manifold dynamics of demographic presence in Nepal. The polities at large are distinct in terms of culture, class and caste. The study focuses on ethnic differences in the context of the recent political development of Nepal. Demographic changes have profound effects on the society, economy, and people of a political institution. Nepal is a multi-ethnic country with a history of ethnic discrimination over the centuries because of racial differences imbibed in political and social affairs of the Nepalese. Demographic changes in Nepal have occurred under unique circumstances within a both a historical context and a contemporary and comparative perspective against other countries have encountered. The article encompasses the factors such as cultural harmony, integrity, and equity to analyze cultural differences and racial realities in the scenario of the postmodern era. The paper unfolds the pages of underrepresentation of the marginalized communities and overrepresentation of Indo-Aryan groups and Newar in the polity.